Hydrogen sulfide alleviates toxic effects of arsenate in pea seedlings through up-regulation of the ascorbate-glutathione cycle Possible involvement of nitric oxide - Singh, Vijay Pratap (Journal of plant physiology, 2015)
Copyright © 2015 Elsevier GmbH. All rights reserved.